Climate Emergency: UK Universities' Declarations and Their Role in Responding to Climate Change - Latter, Briony; Capstick, Stuart (Frontiers in Sustainability, 2021)
On April 17, 2019, the University of Bristol became the first university in the United Kingdom (UK) to declare a climate emergency. Against a backdrop of high visibility and public concern about climate change, as well as climate emergency declarations from other sectors, another 36 UK universities followed suit over the next year. This paper explores what these climate emergency declarations show about how UK universities are responding to climate change and wider sustainability concerns, as well as how they view and present themselves in relation to this. Critical Discourse Analysis of the declarations allowed for in-depth scrutiny of the purpose and wider social context of the documents, demonstrating that they function as promotional statements, as presenting a collective voice, and showing a commitment from the universities to action. We argue that while these provide the potential for advancing sustainability within the sector, the tendency to use declarations as publicity and promotional material does detract from new commitments and action. The research contributes to the discussion around the role of universities as institutions with a responsibility both to act on climate change and to shape the broader societal response to it. It also provides insights as to how future research can evaluate universities in relation to their commitments and strategies, and provides suggestions to help ensure they live up to the promises and intentions that they have publicly made.